A Systematic Review of Maternal and Child Health Policies in Addressing Stunting: Trends and Challenges - Ramlan, Pratiwi; Sukri, Phill; Abdullah, Muh. Tang; Ibrahim , Muhammad Akmal; Ahmad , Jamaluddin; Adri , Khaeriyad (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Introduction: Stunting, recognized as a prominent global health issue, particularly in low-income countries, arises from persistent undernutrition and frequent infections, adversely impacting children's physical development, cognitive abilities, and future economic productivity. Notwithstanding the implementation of various maternal and child health strategies designed to mitigate stunting, its incidence remains alarmingly high, exhibiting differential efficacy across diverse contexts due to obstacles in policy execution, accessibility issues, and socio-cultural influences. Methods: This study utilized a research methodology that included a bibliometric analysis of publications retrieved from the Scopus Database relating to maternal and child health policies in reducing stunting prevalence using the keywords “maternal and child health policies” and “stunting”. The findings were directly related to the research topic, revealing a total of 154 articles published from 2004 to 2023. The criteria set emphasized articles written in English, with the data obtained exported in CSV format. VOS viewer version 1.6.17 was used for bibliometric analysis in this study. Results: The results showed a significant increase in publications addressing the relationship between health policies and stunting prevalence. Academic discussions on policy and stunting have also increased, especially in the fields of medicine and nursing, which reveal the health impacts on stunted children. Data analysis from various studies emphasized the importance of evidence-based strategies that combine medical interventions with structural, social and economic transformation. Conclusion: In conclusion, this review emphasizes the importance of collaboration between various sectors, including health, education, and agriculture, in addressing stunting. Policymakers should consider establishing dedicated funding streams through public-private partnerships to ensure the sustainability of stunting prevention programs. Implementing regulatory frameworks that mandate intersectoral collaboration between health, education, and agriculture sectors can enhance policy coherence and resource optimization. Furthermore, adopting performance-based incentives for local health agencies may encourage more effective policy implementation and service delivery.